A self-supported NiMoS4 nanoarray as an efficient 3D cathode for the alkaline hydrogen evolution reaction. Issue 32 (27th July 2017) - Wang, Weiyi; Yang, Lin; Qu, Fengli; Liu, Zhiang; Du, Gu; Asiri, Abdullah M.; Yao, Yadong; Chen, Liang; Sun, Xuping
Abstract : A NiMoS4 nanoarray on Ti mesh (NiMoS4 /Ti), developed via topotactic hydrothermal conversion from its Ni(OH)2 nanoarray (Ni(OH)2 /Ti), drives hydrogen-evolution current densities of 10 and 50 mA cm −2 at overpotentials of 194 and 263 mV in 0.1 M KOH, respectively. Abstract : Developing non-noble-metal hydrogen evolution reaction electrocatalysts with high activity is critical for future renewable energy systems. Here we describe the development of a self-supported NiMoS4 nanosheet array on Ti mesh (NiMoS4 /Ti) through a facile two-step hydrothermal strategy. As a 3D nanoarray electrode for electrochemical hydrogen evolution, NiMoS4 /Ti shows exceptionally high catalytic activity and strong durability in 0.1 M KOH (pH: 13). It needs overpotentials of only 194 and 263 mV to drive geometrical catalytic current densities of 10 and 50 mA cm −2, respectively. Moreover, such a catalyst also demonstrates superior long-term stability with a high turnover frequency of 0.75 mol H2 s −1 at an overpotential of 148 mV. Density functional theory calculations suggest a more favorable hydrogen adsorption free energy on the NiMoS4 surface.